Jak to było naprawdę z sukcesami wywiadu Stasi na Zachodzie? - Müller-Enbergs, Helmut (Pamięć i Sprawiedliwość, 2014)
The author has attempted to assess the effectiveness of activity of Hauptverwaltung Aufklärung (HV A), i.e the intelligence unit of the GDR Ministry for State Security (MfS/ Stasi). The circumstances of the unification of Germany and the liquidation of the GDR would indicate that the primary task of HV A, that is defence of state interests, was not accomplished. Detailed analysis presented by the author shows that the final assessment of the effectiveness of HV A is more complicated. The author suggested an evaluation model which in his opinion is useful to review the work of intelligence services, assuming that the degree of accomplishment of the intelligence objectives was the main indicator of the effectiveness and success of the HV A activities. Effectiveness of work of the intelligence should also have translated into long-term existence and activity of the service. The third indicator was defined by the author as the customer and employee satisfaction. In this case, it concerned, among other things, the loyalty and sense of identification of the HV A employees and agents. The author’s conclusions also concern the possibility of comparing the activity of HV A against the work of other intelligence services.